Ankle-Brachial Index Is Independently Associated With Cardiovascular Outcomes and Foot Ulcers in Asian Patients With Type 2 Diabetes Mellitus - Yang, Ming-Chi; Huang, Yu-Yao; Hsieh, Sheng-Hwu; Sun, Jui-Hung; Wang, Chih-Ching; Lin, Chia-Hung (Frontiers in Endocrinology, 2021)
Background and aims: The ankle-brachial index (ABI) is an efficient tool for objectively documenting the presence of lower-extremity peripheral arterial disease (PAD). The factors predictive of cardiovascular outcomes and diabetic foot ulcers were not clear from the ABI examination in Taiwanese patients with type 2 diabetes mellitus (DM). Methods: We enrolled 482 patients with type 2 DM who regularly visited the outpatient department of Chang Gung Memorial Hospital and ABI and brachial-ankle pulse wave velocity (ba-PWV) examinations. Age, gender, PAD symptoms, history of chronic disease, family history of chronic disease, lifestyle data (smoking, alcohol consumption, and exercise), height, weight, waistline, monofilament test results, dorsalis pedis artery test results, and foot ulcer status were studied. Results: There were 104 (22%) patients (mean age, 67 years) with the ABI value <1.0. These patients with low ABI (ABI<1.0) had a significantly older age (p=0.001), higher delta PWV (p<0.001), a significantly higher rate of stroke (p=0.007), myocardial infarction (p=0.016), and foot ulcer (p=0.039). In a multivariable analysis model, the adjusted odds ratio (aOR) for myocardial infarction, stroke, and foot ulcers associated with low ABI were 1.219 (0.397-3.743, p=0.729), 1.204 (0.556-2.610, p=0.638), and 2.712 (1.199-6.133, p=0.017), respectively. The patients with low PWV (PWV<1400) were significantly younger (p<0.001) and had a lower rate of hypertension (p<0.001), stroke (p=0.027), and family history of dialysis (p=0.041). Conclusions: Our results demonstrated that values of ABI were independently associated with diabetic foot in patients with type 2 DM. Screening patients with type 2 DM using ABI, a simple and noninvasive marker, may help identify patients at high risk of diabetic foot.